Confronting school violence: a synthesis of six decades of research - Turanovic, Jillian J. (Cambridge elements. Elements in criminology, 2022)
School violence is a significant social concern. To better understand its sources, a comprehensive meta-analysis of the school violence and victimization literature was undertaken. Across 761 studies, the relative effects of 30 different individual, school, and community level correlates were assessed (8,790 effect size estimates). Violence and victimization were conceptualized broadly to include various forms of aggression and crime at school. The results revealed that the strongest correlates of school violence perpetration were antisocial behavior, deviant peers, antisocial attitudes, victimization, and peer rejection; and that the strongest correlates of school victimization were prior/other victimization, social competence, risk avoidance, antisocial behavior, and peer rejection. Extracurricular activities and school security devices had among the weakest associations in the meta-analysis, and several traditional criminological predictors did not perform well in the school context. We conclude with recommendations for theory, future research, and policy.